(untitled) (Sustainability in Debate, 2018)
Mangroves are important ecosystems that sometimes may have intense interaction with irregular unplanned urbanization environments. The objective of this work is to analyze the perceptions of the environment, psychological conditions and inhabitants’ quality of life within irregular occupations in the mangrove areas of the Baixada Santista (SP). Thirty residents of a mangrove neighborhood were recruited and answered the following instruments: World Health Organization Quality of life - Abbreviated Scale (WHOQOL - Bref), Adult Self-Report for ages 18-59 (ASR) and an environmental perception survey. The data descriptive analysis indicated: environmental perception marked by positive values attributed to the mangrove, importance of preservation, appointments of various species and physical components; problems of clinical psychology affecting young women, and quality of life classified as good (physical, social and psychological domains) and regular (environmental domain). The accentuated environmental perception and the regularization of the occupations may be related to the good health and quality of life of the participants.